1984
DOI: 10.1093/nar/12.11.4757
|View full text |Cite
|
Sign up to set email alerts
|

A ribosome binding site sequence is necessary for efficient expression of the distal gene of a translationally-coupled gene pair

Abstract: Expression of trpB and trpA of the Escherichia coli tryptophan operon is shown to be "translationally coupled", i.e., efficient translation of the t coding region is dependent on prior translation of the trpB coding region and termination of translation at the trpB stop codon.. To examine the dependence of trpA expression on the ribosome binding site sequence in the distal segment of t, deletions were produced that replaced this tpB sequence. Analysis of trpA expression in these deletion mutants establ4ished t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 37 publications
3
66
0
Order By: Relevance
“…Recent experiments from other laboratories (51,68) (i) With polycistronic procaryotic transcripts, where occlusion can indeed occur, the inhibitory effect of an overlapping upstream cistron is sometimes only two-or threefold (11,19,61). In eucaryotes, on the other hand, initiation at a downstream ATG codon is completely suppressed when it is overlapped by an upstream cistron (8,35,40,54,65).…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments from other laboratories (51,68) (i) With polycistronic procaryotic transcripts, where occlusion can indeed occur, the inhibitory effect of an overlapping upstream cistron is sometimes only two-or threefold (11,19,61). In eucaryotes, on the other hand, initiation at a downstream ATG codon is completely suppressed when it is overlapped by an upstream cistron (8,35,40,54,65).…”
Section: Discussionmentioning
confidence: 99%
“…Mutational analysis showed that repA is translationally coupled to repB, a gene encoding a small leader peptide, and that there is almost no expression of repA in the absence of expression of repB. The stop codon of repB overlaps the repA start codon, an arrangement that is generally considered to be most efficient for coupled genes since the ribosome terminating translation of the upstream gene can reinitiate at the downstream one without dissociating from the mRNA (2,8,33,41,48). However, this was found not to be the case for the IncB plasmid pMU720, whose coupled genes, repB and repA, overlap by 10 bp.…”
Section: Discussionmentioning
confidence: 99%
“…The expected fusion protein products for each construct are indicated to the right. change in 32 stability during the heat-shock response, we constructed a reporter system by using translational coupling that occurs at the trpB-trpA junction, in which translation of the downstream gene (trpA) depends largely on complete translation of upstream trpB (36). The entire rpoH gene including promoters but omitting the stop codon (UAA) was fused with the 92-bp trpBA junction and with lacZ (Fig.…”
Section: Methodsmentioning
confidence: 99%